AN INTEGRATED AIGAR MODEL USING DESIGN-BASED RESEARCH COMBINING ARTIFICIAL INTELLIGENCE, GAMIFICATION, RELIGIOSITY, AND CRITICAL LITERACY - Widodo, Hadi; Bahri, Samsul; Tumiyem, Tumiyem (LPPM Universitas Jambi, 2026)
The integration of digital technology in Islamic higher education remains fragmented and often overlooks the role of religiosity in shaping students’ critical literacy. Existing studies tend to examine artificial intelligence, gamification, and religiosity separately without providing an integrated pedagogical framework. This study aims to develop and validate the AIGaR model by integrating artificial intelligence, gamification, and religiosity to enhance students’ critical literacy. This study employed a design-based research approach involving iterative phases of design, implementation, and evaluation. The participants were students in Islamic higher education institutions. Data were collected using validated instruments measuring critical literacy, learning engagement, and religiosity. The data were analyzed using structural equation modeling to examine relationships among variables and evaluate the effectiveness of the model. The results indicate that the AIGaR model significantly improves students’ critical literacy, particularly in analytical and evaluative skills. Gamification enhances student engagement, while religiosity strengthens reflective and ethical dimensions. The model demonstrates strong validity and reliability across implementation cycles. This study offers a novel integrative AIGaR model that systematically combines artificial intelligence, gamification, and religiosity within a unified learning framework. The findings provide practical implications for educators and curriculum designers to develop technology-enhanced learning that is pedagogically effective, ethically grounded, and contextually relevant in Islamic higher education. However, this study is limited to a specific context and sample size. Future research should examine the model across broader settings and populations.